The Role of the Acid Pocket in Gastroesophageal Reflux Disease. Issue 2 (February 2016) - Mitchell, David R.; Derakhshan, Mohammad H.; Robertson, Elaine V.; McColl, Kenneth E. L.
Abstract : Gastroesophageal reflux disease is one of the commonest chronic conditions in the western world and its prevalence is increasing worldwide. The discovery of the acid pocket explained the paradox of acid reflux occurring more frequently in the postprandial period despite intragastric acidity being low due to the buffering effect of the meal. The acid pocket was first described in 2001 when it was detected as an area of low pH immediately distal to the cardia using dual pH electrode pull-through studies 15 minutes after a meal. It was hypothesized that there was a local pocket of acid close to the gastroesophageal junction that escapes the buffering effect of the meal, and that this is the source of postprandial acidic reflux. The presence of the acid pocket has been confirmed in other studies using different techniques including high-resolution pHmetry, Bravo capsule, magnetic resonance imaging, and scintigraphy. This review aims to describe what we know about the acid pocket including its length, volume, fluid constituents, and its relationship to the lower esophageal sphincter and squamocolumnar junction. We will discuss the possible mechanisms that lead to the formation of the acid pocket and examine what differences exist in patients who suffer from acid reflux. Treatments for reflux disease that affect the acid pocket will also be discussed.